2021
DOI: 10.1007/s10555-021-10006-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolic ecosystem in cancer progression — metabolic plasticity and mTOR hyperactivity in tumor tissues

Abstract: Despite advancements in cancer management, tumor relapse and metastasis are associated with poor outcomes in many cancers. Over the past decade, oncogene-driven carcinogenesis, dysregulated cellular signaling networks, dynamic changes in the tissue microenvironment, epithelial-mesenchymal transitions, protein expression within regulatory pathways, and their part in tumor progression are described in several studies. However, the complexity of metabolic enzyme expression is considerably under evaluated. Alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 393 publications
(400 reference statements)
0
18
0
Order By: Relevance
“…It has been proved that both of mechanical tissue stiffness and metabolic modulation affect directly each other to cause genome-wide changes in epigenetic regulatory states. ECM acts as a metabolic niche in tissue microenvironment, and its targeted therapeutic management might cause metabolic rewiring of tumor cells, and influence crosstalk between nonmalignant and malignant cell phenotypes in the metabolic ecosystem 196 . As far as I know, it is the first time to introduce the mulberry-fish-ponds model to the area of cancer ecology.…”
Section: Exploiting Ecological Principles To Understand Npc Progressionmentioning
confidence: 99%
“…It has been proved that both of mechanical tissue stiffness and metabolic modulation affect directly each other to cause genome-wide changes in epigenetic regulatory states. ECM acts as a metabolic niche in tissue microenvironment, and its targeted therapeutic management might cause metabolic rewiring of tumor cells, and influence crosstalk between nonmalignant and malignant cell phenotypes in the metabolic ecosystem 196 . As far as I know, it is the first time to introduce the mulberry-fish-ponds model to the area of cancer ecology.…”
Section: Exploiting Ecological Principles To Understand Npc Progressionmentioning
confidence: 99%
“…Cancer cells were also shown to induce metabolic changes in stromal cells; these changes allow CAFs to display activities, which support growth and progression of cancer cells. Metabolic adaptation is recognised as a hallmark of cancer [ 38 ]: crosstalk of cancer cells and cells forming the tumour microenvironment results in a metabolic symbiosis during tumour progression [ 54 ]. For example, in an orthotopic mouse model for ovarian carcinoma, glutamine supply of cancer cells was ensured by cancer-associated fibroblasts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies have shown vessel co-option is associated with primary melanoma and organ (brain, lung, and liver) metastases of melanoma (Lugassy et al, 2014;Szabo et al, 2015;Bentolila et al, 2016;Barnhill et al, 2018;Rodewald et al, 2019), which may be an essential factor for poor clinical effectiveness of anti-angiogenic drugs. Secondly, in terms of the resistance mechanism to anti-angiogenic therapy, metabolic symbiosis is also reported in both experimental and clinical studies (Jimenez-Valerio et al, 2016;Sebestyen et al, 2021). Both OXPHOS and glycolysis (metabolic symbiosis) have been identified to be critical for metabolic plasticity in melanoma, driving acquired resistance to anti-angiogenic chemotherapy (Kumar et al, 2021).…”
Section: Mechanisms Of Resistancementioning
confidence: 97%